Ассоциация полимеров с малыми молекулами - Бектуров Есен Абикенович (Наука, 1983)
Экземпляры: КХ (20120913) / Инвентарный номер: 798652 / Цена: 2.40 / Сис.шифр: 547 / Авт.знак: Б 42 / ГРНТИ: 31 / ББК: 24